Case Report: Hyper IgE, but Not the Usual Suspects–Kimura Disease in an Adolescent Female - Ramachandran, Prasanna Venkatesh; Healy, C. Mary; Lambert, Elton M.; Guerra, Deyanara; Curry, Choladda V.; Vogel, Tiphanie P. (Frontiers in Pediatrics, 2021)
Elevated immunoglobulin E (IgE) levels can be associated with infectious, allergic and inflammatory disorders, and rarely as a manifestation of an inborn error of immunity. Here we report the case of an adolescent female who presented with a gradually enlarging neck mass, lymphadenopathy, eosinophilia and highly elevated IgE levels. Laboratory and histopathologic evaluation revealed an unlikely diagnosis of Kimura Disease. We discuss the differential diagnosis of a neck mass with prominent eosinophils on histology, and review support for T-helper type 2 (Th2) cell activation and hyper-IgE in Kimura Disease.